Applications of the matching law to observe shifts in problem behavior: A proof‐of‐concept study. (29th June 2021) - Kronfli, Faris R.; Lloveras, Lindsay A.; Vollmer, Timothy R.
Abstract: We used the matching law to quantify the relation between the relative likelihood of appropriate behavior and problem behavior and the relative likelihood of parent‐delivered reinforcement for those behaviors. First, we conducted an initial descriptive observation in the dyads' homes. Second, we assessed the problem behavior within a clinic where participants were receiving behavior‐analytic services. Third, using behavioral skills training (BST), we taught parents how to implement treatments based on differential reinforcement. Fourth, we conducted a second descriptive observation in the dyads' home. Last, we used the generalized matching law to quantify the relation between the child's response allocation and parent‐delivered reinforcement before and after BST. The relation between the effects of parent‐delivered reinforcement on the relative likelihood of appropriate and problem behavior was well described by the matching law.